2018
DOI: 10.1200/jop.2017.026435
|View full text |Cite
|
Sign up to set email alerts
|

What Every Oncologist Should Know About Geriatric Assessment for Older Patients With Cancer: Young International Society of Geriatric Oncology Position Paper

Abstract: Aging is a heterogeneous process. Most newly diagnosed cancers occur in older adults, and it is important to understand a patient's underlying health status when making treatment decisions. A geriatric assessment provides a detailed evaluation of medical, psychosocial, and functional problems in older patients with cancer. Specifically, it can identify areas of vulnerability, predict survival and toxicity, assist in clinical treatment decisions, and guide interventions in routine oncology practice; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 89 publications
1
108
0
2
Order By: Relevance
“…15 This may be even more relevant in frail elderly patients with ROC, particularly those with PR-ROC given the low response rates observed even in younger and fitter patients. 15 This may be even more relevant in frail elderly patients with ROC, particularly those with PR-ROC given the low response rates observed even in younger and fitter patients.…”
Section: Patients With Roc With a Poor Prognosis And Low Likelihood Omentioning
confidence: 99%
See 3 more Smart Citations
“…15 This may be even more relevant in frail elderly patients with ROC, particularly those with PR-ROC given the low response rates observed even in younger and fitter patients. 15 This may be even more relevant in frail elderly patients with ROC, particularly those with PR-ROC given the low response rates observed even in younger and fitter patients.…”
Section: Patients With Roc With a Poor Prognosis And Low Likelihood Omentioning
confidence: 99%
“…There are several reliable tools available with which to assess elderly patients and a comprehensive geriatric assessment screen for vulnerability should be part of the patient workup to identify this frail and vulnerable subset of patients. 15,16 However, it is worth noting that an expert panel could not endorse one tool over another. 17,18 It is beyond the scope of this article to discuss geriatric assessments, but they all essentially include an assessment of several domains, including physical functioning, psychosocial factors, concurrent medications, comorbidities, nutrition, and cognition.…”
Section: Patients With Roc With a Poor Prognosis And Low Likelihood Omentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive geriatric assessment (CGA) can be helpful in this setting. [8] CGA is a set of validated tools to assess domains such as physical function, nutritional status, medications, social support, cognitive function, and psychological health [9]. Studies have shown that a CGA provides a more accurate determination of functional age in older patients with cancer compared to chronological age or physician-assigned performance status alone [2].…”
Section: Introductionmentioning
confidence: 99%